Integrated transcriptomic and single-cell RNA-seq analysis identifies CLCNKB, KLK1 and PLEKHA4 as key gene of AKI-to-CKD progression - Zeng, Fanhua; Yang, Zhenhua; Wang, Zufeng (Frontiers in Immunology, 2025)
BackgroundStudies have demonstrated a significant connection between acute kidney injury (AKI) and chronic kidney disease (CKD). The purpose of this study was to identify biomarkers linked to the advancement of AKI and CKD, aiming to offer new targets and insights for treating and intervening in these conditions.MethodsInitially, candidate genes were identified by overlapping the results from differential expression analyses of AKI and CKD. Biomarkers were subsequently identified using machine learning algorithms, receiver operating characteristic curve analysis, expression analysis and experimental verification. Functional enrichment, drug prediction analyses and immune cells infiltration were conducted to investigate the functional mechanisms of the identified biomarkers. Furthermore, single-cell analyses were performed to examine the trends of biomarker expression across different cell types.ResultsCLCNKB, KLK1 and PLEKHA4 were identified as biomarkers by the screening. Subsequently, enrichment analysis showed that CLCNKB was notably enriched in oxidative phosphorylation and the degradation of valine, leucine, and isoleucine in both AKI and CKD datasets. CLCNKB, KLK1 and PLEKHA4 were found to be significantly associated with multiple immune cell types. The regulatory network indicated that PLEKHA4 might play a more important role in the progression of AKI and CKD. Furthermore, it was discovered that CLCNKB, KLK1, and PLEKHA4 are commonly targeted by tetrachlorodibenzodioxin. Finally, in the single-cell data analysis, Type A intercalated cell and Collecting duct-principal cell were identified as the key cells. It was observed that the expression trends of these biomarkers were different under different differentiation states of the key cell subpopulations.ConclusionCLCNKB, KLK1 and PLEKHA4 were identified as biomarkers related to the development of AKI and CKD in this study, and new ideas were provided for the research on the potential mechanisms of the progression of AKI and CKD.